Analysis of endorphin massage and deep breathing relaxation on reducing back pain in pregnant women - Retno Palupi Yonni Siwi; Erma Retnaningtyas; Anggrawati Wulandari; Musabbiha Dg. Masiga (Institute of Accounting Research and Novation (IARN), 2026)
One of the physiological problems that pregnant women often complain about is back pain. Lack of treatment by pregnant women in overcoming back pain causes mothers to feel anxious and worried. The purpose of this study was to determine the effect of endorphin massage and deep breathing relaxation on reducing back pain in pregnant women. This study design was pre-experimental, with a two-group pretest-posttest approach. Respondents were taken using a purposive sampling technique with a sample of 30 respondents. The independent variables were endorphin massage and deep breathing relaxation and the dependent variable was the reduction in back pain. The results of the statistical test used an independent t-test. The results showed that before the endorphin massage, most pregnant women experienced severe back pain, as many as 10 respondents (66.6%), and after the endorphin massage, it was known that almost all respondents had no pain, as many as 14 respondents (93.3%). Almost all respondents before the deep breathing relaxation experienced severe pain, as many as 14 respondents (93.3%), and after the deep breathing relaxation, most respondents had no pain, as many as 11 respondents (73.3%). The data analysis results showed a significance level of 0.000 < α = 0.05, so H0 was rejected and H1 was accepted. This means that endorphin massage and deep breathing relaxation have an effect on reducing back pain in pregnant women because they can promote relaxation and minimize the sensation of pain.